Analisis Pengaruh Loyalitas Karyawan, Gaya Kepemimpinan Dan Product Knowledge Terhadap Kinerja Karyawan CV Indah Makmur Surabaya - Christine, Priscilla Yohana (Research Journal of Social Science and Economics, 2025)
In today's highly competitive business environment, high employee performance is the main goal of many organizations. The success of employee performance achieved by the organization is influenced by the level of employee performance individually or in groups. Competent employees get a favorable impression of employees who are able to help the company adapt to all circumstances. In addition, the management style used in the company affects staff performance. Product knowledge is also needed by employees to know how to make good product materials and use certain stitches so they can market them properly. Employees who understand product information make work easier and improve employee performance. The purpose of this study was to examine the effect of loyalty, leadership style and product knowledge on employee performance at CV Indah Makmur Surabaya. This research is a quantitative descriptive study using a survey method that collects data from respondents using a questionnaire. The population of this study consisted of workers who worked at Indah Makmur Convection and 31 workers who had experience working at Indah Makmur Convection. Samples were collected using a non-probability based sampling method. The data in this study were analyzed using classical acceptance tests, several linear regression tests and hypothesis testing. The results of the t-test of this study found that there was a partially significant effect between employee loyalty and employee performance, secondly, leadership style had a partially significant effect on employee performance, and thirdly, product knowledge had a partially significant effect.